Analysis of students' creative thinking ability in solving quadrilateral mathematical problems - Wharyanti Ika Purwaningsih; Riawan Yudi Purwoko (State Islamic University of North Sumatra, 2025)
This study aims to analyse the creative thinking abilities of eighth-grade junior high school students in solving mathematical problems related to quadrilaterals. The study employed a qualitative exploratory descriptive design with purposive sampling, involving two students with high mathematical ability. The test instruments were validated by mathematics education experts to ensure content validity and alignment with creative thinking indicators. Data were collected through problem-solving tests, in-depth interviews, and field notes, and were analysed using the Miles and Huberman model, which consists of data reduction, data display, and conclusion drawing. The results showed that both students met all indicators of creative thinking